Challenges and considerations of applying nature-based solutions in low- and middle-income countries in Southeast and East Asia. Issue 1 (10th December 2020) - Lechner, Alex M.; Gomes, Rachel L.; Rodrigues, Lucelia; Ashfold, Matthew J.; Selvam, Sivathass Bannir; Wong, Ee Phin; Raymond, Christopher M.; Zieritz, Alexandra; Sing, Kong Wah; Moug, Peter; Billa, Lawal; Sagala, Saut; et al.
Abstract: Low- and middle-income countries in Southeast and East Asia face a range of challenges related to the rapid pace of urbanisation in the region, the scale of pollution, climate change, loss of ecosystem services and associated difficulties for ecological restoration. Possible pathways towards a more sustainable future lie in the applications of nature-based solutions (NBS). However, there is relatively little literature on the application of NBS in the region, particularly Southeast Asia. In this paper we address this gap by assessing the socio-ecological challenges to the application of NBS in the region – one of the most globally biodiverse. We first provide an overview and background on NBS and its underpinnings in biodiversity and ecosystem services. We then present a typology describing five unique challenges for the application of NBS in the region: (1) Characteristics of urbanisation; (2) Biophysical environmental and climatic context; (3) Environmental risks and challenges for restoration; (4) Human nature relationships and conflicts; and (5) Policy and governance context. Exploiting the opportunities through South-South and North-South collaboration to address the challenges of NBS in Southeast and East Asia needs to be a priority for government, planners and academics. Highlights: Most research on Nature-Based Solutions (NBS) is in high income nations with low population growth rates and regulated urban planning. Urban blue-green infrastructure is being degraded in low and middle-income Southeast and East Asian countries. Applications of NBS in the region need to address the unique socio-ecological challenges. We provide an overview of key knowledge gaps to support the implementation of NBS.